A Novel Dynamically Self Tuned Force/Torque Observer Formulation for Human Interaction in Collaborative Robotic Applications - Inci, Hazin; Selim, Erman; Tatlıcıoğlu, Enver; Zergeroğlu, Erkan; Taskingollu, Sule (Elsevier, 2024)
In this study, we present the design and numerical implementation of a novel force/torque observer formulation, for collaborative robotic tasks that might require human interaction. Specifically a dynamically self-adjusting robust observer is introduced to ensure practical estimation of the end effector force/torque values of a robotic manipulator. The stability of the observer is guaranteed via Lyapunov based arguments and simulation studies implementation on a two link robotic manipulator are presented to demonstrate proof-of-concept. Copyright (c) 2024 The Authors.
5th IFAC Workshop on Cyber-Physical Human Systems -- DEC 12-13, 2024 -- Antalya, TURKEY
Keywords: Force observer; robot manipulator; human interaction